Analysis of competitiveness and competitive advantages in today's market conditions - Pavliuk, Tetiana; Noda, Veronika (Management and Entrepreneurship: Trends of Development, 2020)
The article is devoted to the issues of competitiveness analysis, by which it is possible to evaluate the competitive advantages and disadvantages and to build a strong competitive strategy. The purpose of the article is to research, analyze and identify the main directions of increasing the level of competitiveness of the enterprise under research. The main concepts of enterprise competitiveness are considered in the article and the analysis of the competitive environment of LLC “MIG” LLC is presented. The main factors of influence and competitiveness were revealed and recommendations were given to improve the competitive position of enterprises. The main methods of this study are the methods of empirical research, such as observation, comparison, measurement, as well as abstraction, analysis and synthesis, induction and deduction. Today, technologies have tremendous growth rates, consumer needs are growing with maximum geometric progression, so the task of each enterprise is to be competitive, to have competitive advantages, in order to survive in the world market. Despite the fact that the concept of competitiveness has been studied for a long time, there are issues that need to be studied as quickly as the market allows, in order for enterprises to be able to maximize profits, so the question of competitiveness market analysis is relevant for every enterprise today. In today's global economic development, which is characterized by competition and extremely fast pace of development of the organization, an important component of competition can be considered a vector of orientation to the needs of clients and work in the field of the client. The desire to succeed in customer service is maximized, so there is a growing need for practical guidance on how to focus on customer needs and interests, which will help to maximize competitiveness in the market. The research has practical value, evidenced by recommendations given for improving the competitive position of an enterprise operating in the Ukrainian market by analysing the competitiveness, competitive environment and the vector for its development.JEL Classification: L11, M11, D41.